The influence of Cr doped TiO² on the optical property and photocatalytic activity under sunlight irradiation / Siti Zulaikha Suhaili … [et al.] - Suhaili, Siti Zulaikha; Yaakob, Muhamad Kamil; Saaid, Siti Irma Yuana; Jais, Umi Sarah (Penerbit UiTM (UiTM Press), 2016)
Pure Ti0₂ and Cr doped Ti0₂ (0.1-1.0wt% Cr) nanoparticles were synthesized via sol gel method. This study focuses on narrowing the Ti0₂ band gap energies in order to enhance the photocatalytic efficiency under visible light. The synthesized samples were characterized by X-Ray diffraction method (XRD), field emmision (FESEM) and also UV-Vis diffuse reflectance spectroscopy (DRS).The photocatalytic activity under sunlight irradiation was demonstrated by photocatalytic decomposition of methylene blue in water using UV/Vis spectrophotometer. The XRD analysis of pure Ti0₂ and doped Ti0₂ calcined at 500°C showed a mixture of anatase and rutile phases with decreasing crystallites size from 13.3nm to 11.6nm as the concentration of Cr was increased. The anatase-rutile phase transformation increased from 28.8% to 57.4%. An indication shows that at 0.75wt%, Cr the anatase and rutile phases have equal composition percentage. This study demonstrated that band gap energy of Ti0₂ was reduced with Cr doping which could enhance the photocatalytic efficiency. Sample containing 1.0wt% exhibit the lowest optical band gap energy at 2.86 eV. The optimum chromium doping concentration was found to be at 0.1 wt% Cr corresponding to band gap energy of 2.87 eV and degradation rate of 84%.